ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA (Studi Empiris Perusahaan di Jakarta Islamic Index) - Ali Muhayatsyah; Nur Fatia (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2019)
Financial ratio analysis is one of the techniques of financial statement analysis. Financial ratio analysis can be used to predict changes in earnings in the future. The research that will be conducted aims to test the ability of financial ratios to predict changes in earnings in the future. Prediction of profit changes in this study uses 31 financial ratios as independent variables and relative earnings changes as the dependent variable. The samples to be tested are companieslisted in the Jakarta Islamic Index for the 2014-2017 period by purposive sampling. Data analysis using the Stepwise Regression method, namely regression analysis that selects the variables that will be members of the regression equation by making selections based on the tolerance criteria of the variables. The conclusion of this study is that there are several financial ratios to predict changes in earnings in the future. These ratios OINIBT (Operating Income toNet Income Before Taxes) have a positive effect on future earnings predictions, OITL (Operating Income to Total Liabilities) has a negative effect on future earnings predictions, CATA (Current Assets to Total Assets) have a positive effect on earnings predictions in the future, and WCTA (Working Capital to Total Assets) has a negative effect on future earnings predictions.